The Spatial Variation of Registered Divorce Cases for Residents of Urban Centers in Erbil Governorate - Hiwa Sadiq Saleem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Divorce is one of the social problems whose rates have increased rapidly in recent years in the study area. Which led to many social, economic and legal problems, and based on that, the research aims to study the spatial variation and temporal change of the cases of divorce registered for residents of urban centers in the governorate of Erbil, based on measurements related to the phenomenon, as well as knowing the reasons leading to that discrepancy, relying on the methodology Inductive. The study included three axes in addition to the introduction, where the first axis was devoted to defining the study area and its subject, while the second axis was devoted to studying the development and distribution of divorce cases at the governorate level and its administrative units (districts), while the third axis dealt with the factors and causes that led to the increase in divorce cases in the study area. He concluded the study with a number of conclusions and recommendations.